Maternal Health Outcomes and Complications from Multiple Caesarean Sections: An Analysis of Prevalence and Long-Term Risks: - - Jadhav, Shilpa; sharma, Rituja (Journal of Neonatal Surgery, 2025)
The research examines the prevalence, risk, and decision-making determinants of multiple Caesarean sections among women in Maharashtra, India. Increased global Caesarean section rates have evoked concerns regarding their long-term maternal health effects, especially for multiple procedures. The research seeks to evaluate the prevalence of multiple Caesarean sections, examine complications such as uterine rupture and placental abnormality, and analyze awareness and decision-making determinants affecting repeat procedures. Using a mixed-methods design, the research draws on a standardized questionnaire administered to 41 women who had C-sections, using convenience sampling. Statistical inference using MS Excel and SPSS involves descriptive statistics, ANOVA, and regression models for the determination of demographic and healthcare-related determinants. Results indicate substantial differences in the prevalence of multiple C-sections among demographic groups, with younger women aged between 18 and 30 years having more procedures on average. Urban participants had higher reported access to healthcare compared to rural participants. Still, no statistically significant variations were found across age groups in ANOVA analysis. The research emphasizes the importance of specific interventions to mitigate inequalities in the access of healthcare and to reinforce maternal health management practices for women with multiple Caesarean sections. It recommends enhancing the awareness of women regarding risks related to repeat Caesarean procedures as well as promoting evidence-based obstetric practices.